Straits settlements Blue Book miscellanea (imports/exports) 1884-1885 vol.18-20 (Great Britain : Public Record Office, 1971)
Mengandungi'Straits Settlements. Blue Book for the year 1884-85';'report on Straits Settlements Blue Book for the year 1884-85'; lampiran kepada imports and exports.